Flame-retardant gel polymer electrolyte supported by diaphragm, preparation method and application thereof
Patent Information
- Application Number
- CN202611520477.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-29
- Publication Date
- 2026-10-30
AI Technical Summary
现阶段主流的PVDF-HFP凝胶电解质多采用DMF有机溶剂溶解铸膜工艺制备,依托聚合物物理吸附作用形成凝胶体系,虽具备良好的成膜性能,但仍存在诸多技术短板:该类聚合物骨架本身不具备含磷阻燃结构,本征阻燃性能差;同时制备过程易残留有机溶剂,且体系功能单元负载含量受限,长期循环过程中凝胶骨架溶胀稳定性不足,难以兼顾电池高安全性、高能量密度与长循环稳定性的双重发展需求
[0036]本申请提供一种隔膜支撑的阻燃型凝胶聚合物电解质及其制备方法和应用,该隔膜支撑的阻燃型凝胶聚合物电解质包括隔膜基体及负载于隔膜基体表面和/或孔道内部的交联凝胶层;交联凝胶层包括聚合物和吸附于聚合物内部的锂盐电解液;聚合物包括磺酸锂结构单元、刚性结构单元和柔性结构单元,且刚性结构单元的磷元素含量高于柔性结构单元。本申请通过差异化磷含量的双含磷结构协同增效:高磷密度的刚性结构单元依托磷酸酯基团形成致密的聚合物交联网络,既可有效阻断热传导路径,赋予电解质优异的阻燃性能,又可通过刚性链段的骨架约束作用,抑制凝胶电解液过度溶胀,提升结构稳定性;柔性结构单元中醚氧链段可与发生配位作用,提高聚合物网络与电解液的亲和性,并有利于锂离子传输。同时,聚合物中的磺酸锂结构单元可构建连续的锂离子传输通道,优化锂离子迁移行为,并有效缓解锂金属负极的界面副反应,改善电极与电解质的界面相容性与界面稳定性。综上,本申请通过三种功能结构单元的协同匹配,使所述隔膜支撑的阻燃型凝胶聚合物电解质同时兼具高离子电导率、优异阻燃性能、耐溶胀特性及良好的电极界面稳定性,综合性能显著提升。
Smart Images

Figure CN123018099A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of lithium battery electrolytes, specifically relating to a membrane-supported flame-retardant gel polymer electrolyte, its preparation method, and its application. Background Technology
[0002] Lithium batteries are widely used in many fields such as new energy vehicles, energy storage power stations, consumer electronics, and aerospace due to their outstanding advantages of high energy density and long cycle life. Among them, lithium metal batteries and high-voltage lithium-ion batteries have excellent potential for high energy density development. However, most commercial lithium batteries currently use traditional liquid electrolytes, whose inherent defects severely restrict the safety performance and cycle stability of the batteries: liquid electrolytes are highly fluid and prone to leakage and flammability. Under harsh conditions such as high temperature and overcharging, they are prone to thermal runaway, causing fires, explosions, and other safety accidents. At the same time, the interface compatibility between liquid electrolytes and lithium metal anodes is poor, which easily leads to serious interface side reactions. This not only accelerates battery capacity decay but also causes uneven lithium deposition, greatly reducing the service life and safety of the battery.
[0003] Gel polymer electrolytes can immobilize liquid electrolytes through a polymer network, effectively reducing the free-flowing electrolyte within the system. While maintaining high ionic conductivity, they significantly improve the drawbacks of traditional liquid electrolytes, such as easy leakage and flammability, making them one of the core preferred materials for high-performance and safe lithium batteries. Currently, most mainstream PVDF-HFP gel electrolytes are prepared using DMF organic solvent dissolution casting technology, relying on the physical adsorption of polymers to form a gel system. Although they have good film-forming properties, they still have many technical shortcomings: the polymer backbone itself does not have a phosphorus-containing flame-retardant structure, resulting in poor intrinsic flame retardancy; at the same time, the preparation process easily leaves organic solvent residues, and the functional unit loading content of the system is limited, leading to insufficient swelling stability of the gel backbone during long-term cycling, making it difficult to simultaneously meet the dual development requirements of high safety, high energy density, and long-cycle stability of batteries.
[0004] Therefore, developing a gel polymer electrolyte that combines high ionic conductivity, excellent flame retardancy, good interfacial stability, and swelling resistance is of great research significance and application value for improving the overall performance of lithium batteries. Summary of the Invention
[0005] This application provides a diaphragm-supported flame-retardant gel polymer electrolyte, its preparation method, and its application. The diaphragm-supported flame-retardant gel polymer electrolyte has high ionic conductivity, excellent flame-retardant properties, good interfacial stability, and swelling resistance.
[0006] This application provides a membrane-supported flame-retardant gel polymer electrolyte, comprising a membrane substrate and a cross-linked gel layer loaded on the surface and / or inside the pores of the membrane substrate; the cross-linked gel layer comprises a polymer and a lithium salt electrolyte adsorbed within the cross-linked network of the polymer; the polymer comprises lithium sulfonate structural units, rigid structural units, and flexible structural units; the rigid structural unit comprises a first phosphorus-containing structural unit, and the flexible structural unit comprises a second phosphorus-containing structural unit and an ether oxygen structural unit; the mass percentage of phosphorus in the rigid structural unit is greater than the mass percentage of phosphorus in the flexible structural unit.
[0007] In some embodiments of this application, based on the total mass of the polymer, the mass percentage of lithium sulfonate structural units is 5% to 25%, the mass percentage of rigid structural units is 15% to 40%, and the mass percentage of flexible structural units is 35% to 70%.
[0008] And / or, the mass percentage of phosphorus in the rigid structural unit is 10%~14%;
[0009] And / or, the phosphorus content in the flexible structural unit is 5% to 8% by mass.
[0010] In some embodiments of this application, the first phosphorus-containing structural unit includes a first acrylate structural unit and a first ammonium phosphate structural unit; the second phosphorus-containing structural unit includes a second acrylate structural unit and a second ammonium phosphate structural unit.
[0011] And / or, the lithium sulfonate structural unit includes a lithium 2-acrylamide-2-methylpropanesulfonate structural unit.
[0012] In some embodiments of this application, the membrane substrate includes at least one of olefin porous membrane, ceramic-modified polyolefin porous membrane, and polyimide porous membrane;
[0013] And / or, the thickness of the membrane substrate is 9~40μm, and the porosity is 35%~70%;
[0014] And / or, the lithium salt in the lithium salt electrolyte is selected from... At least one of LiFSI, LiTFSI, LiDFOB, LiBOB, and LiBF4;
[0015] And / or, the concentration of lithium salt in the lithium salt electrolyte is 0.8-1.5%. .
[0016] This application also provides a method for preparing the above-mentioned membrane-supported flame-retardant gel polymer electrolyte, comprising the following steps:
[0017] S1. Prepare a mixture containing lithium sulfonate monomer, phosphorus-containing rigid monomer, and phosphorus-containing flexible monomer; immerse the membrane substrate in the mixture for copolymerization and crosslinking reaction to form a polymer on the surface and / or inside the pores of the membrane substrate, thereby obtaining a membrane-supported flame-retardant gel polymer electrolyte matrix.
[0018] The lithium sulfonate monomer and the phosphorus-containing rigid monomer both contain unsaturated bonds, and the phosphorus-containing flexible monomer contains unsaturated bonds and ether oxygen bonds. The phosphorus element mass percentage content in the phosphorus-containing rigid monomer is greater than the phosphorus element mass percentage content in the phosphorus-containing flexible monomer.
[0019] S2. Immerse the membrane-supported flame-retardant gel polymer electrolyte matrix into a lithium salt electrolyte, so that the polymer cross-linking network adsorbs the lithium salt electrolyte, thereby obtaining the membrane-supported flame-retardant gel polymer electrolyte.
[0020] In some embodiments of this application, based on a total mass of all monomers in the copolymerization crosslinking reaction of 100 parts, the phosphorus-containing rigid monomer is 15-40 parts, the phosphorus-containing flexible monomer is 35-70 parts, and the lithium sulfonate monomer is 5-25 parts.
[0021] And / or, the lithium sulfonate monomer comprises lithium 2-acrylamido-2-methylpropanesulfonate;
[0022] And / or, the phosphorus-containing rigid monomer includes acrylate rigid monomer and partially ammonium-salted acrylate rigid monomer, and the phosphorus-containing flexible monomer includes acrylate flexible monomer and partially ammonium-salted acrylate flexible monomer;
[0023] The preparation process of the partially ammonium-salted rigid monomer of acrylate includes: neutralizing the rigid monomer of acrylate with ammonia water, so that some of the phosphate groups in the rigid monomer of acrylate react with ammonia water to obtain the partially ammonium-salted rigid monomer of acrylate.
[0024] The preparation process of the partially ammonium-salted acrylate phosphate flexible monomer includes: neutralizing the acrylate phosphate flexible monomer with ammonia water, so that some of the phosphate groups in the acrylate phosphate flexible monomer undergo a neutralization reaction with ammonia water to obtain the partially ammonium-salted acrylate phosphate flexible monomer.
[0025] And / or, the copolymerization crosslinking reaction is initiated by ultraviolet light in the presence of a photoinitiator.
[0026] In some embodiments of this application, the preparation process of the partially ammonium-treated phosphate acrylate rigid monomer specifically includes the following steps: adding deionized water to the phosphate acrylate rigid monomer to form a dispersion system; adding 5%-25% ammonia water by mass dropwise at 5-30°C; continuously sampling and preparing a 10% aqueous dispersion to detect the pH until the pH of the aqueous dispersion is 6.8-8.0; continuing to stir for 30-120 min; then drying at 40-60°C, and then vacuum drying at 45-65°C and -0.08~-0.095 MPa for 24-48 h to obtain the partially ammonium-treated phosphate acrylate rigid monomer;
[0027] And / or, the preparation process of the partially ammonium-modified phosphate acrylate flexible monomer specifically includes the following steps: adding deionized water to the phosphate acrylate flexible monomer to form a dispersion system, adding 5%-25% ammonia water by mass dropwise at 5-30℃, continuously sampling and preparing a 10% aqueous dispersion to detect the pH until the pH of the aqueous dispersion is 6.8-8.0; continuing to stir for 30-120 min; then drying at 40-60℃, and then vacuum drying at 45-65℃ and -0.08~-0.095 MPa for 24-48 h to obtain the partially ammonium-modified phosphate acrylate flexible monomer;
[0028] And / or, the partially ammonium-treated phosphate acrylate flexible monomer and the partially ammonium-treated phosphate acrylate rigid monomer each independently satisfy at least one of the following indicators:
[0029] 1) Moisture content ≤ 500 ppm;
[0030] 2) The mass percentage of free ammonia or volatile alkaline components is ≤0.10% based on the total mass of monomers;
[0031] 3) Acrylic double bond retention rate ≥95%.
[0032] This application also provides a lithium battery, including a positive electrode, a negative electrode, and a flame-retardant gel polymer electrolyte supported by a separator. The flame-retardant gel polymer electrolyte supported by the separator is located between the positive electrode and the negative electrode. The flame-retardant gel polymer electrolyte supported by the separator includes the above-mentioned flame-retardant gel polymer electrolyte supported by the separator or the flame-retardant gel polymer electrolyte supported by the separator prepared by the above-mentioned preparation method.
[0033] In some embodiments of this application, the positive electrode sheet includes a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode active material; the positive electrode active material includes... , , , , , At least one of them;
[0034] And / or, the negative electrode sheet includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material; the negative electrode active material includes at least one of lithium metal, graphite, silicon carbide, hard carbon, and lithium titanate;
[0035] And / or, the lithium battery includes at least one of lithium metal batteries, high-voltage lithium-ion batteries, high-safety energy storage lithium batteries, and flame-retardant lithium batteries.
[0036] This application provides a membrane-supported flame-retardant gel polymer electrolyte, its preparation method, and its application. The membrane-supported flame-retardant gel polymer electrolyte includes a membrane substrate and a cross-linked gel layer loaded on the surface and / or inside the pores of the membrane substrate. The cross-linked gel layer includes a polymer and a lithium salt electrolyte adsorbed within the polymer. The polymer includes lithium sulfonate structural units, rigid structural units, and flexible structural units, with the phosphorus content of the rigid structural units being higher than that of the flexible structural units. This application achieves synergistic effects through a dual-phosphorus structure with differentiated phosphorus content: the high-phosphorus-density rigid structural units form a dense polymer cross-linked network based on phosphate ester groups, which can effectively block heat conduction paths, imparting excellent flame-retardant properties to the electrolyte, and also inhibit excessive swelling of the gel electrolyte and improve structural stability through the skeletal constraint of the rigid segments; the ether oxygen segments in the flexible structural units can interact with... Coordination occurs, enhancing the affinity between the polymer network and the electrolyte and facilitating lithium-ion transport. Simultaneously, the lithium sulfonate structural units in the polymer can construct continuous lithium-ion transport channels, optimizing lithium-ion migration behavior and effectively mitigating interfacial side reactions at the lithium metal anode, thus improving the interfacial compatibility and stability between the electrode and the electrolyte. In summary, this application, through the synergistic matching of three functional structural units, enables the membrane-supported flame-retardant gel polymer electrolyte to simultaneously possess high ionic conductivity, excellent flame-retardant properties, swelling resistance, and good electrode interfacial stability, resulting in a significant improvement in overall performance. Attached Figure Description
[0037] Figure 1 Examples 1-5 and Comparative Examples 1-7 of this application / Li battery capacity retention rate after 250 cycles;
[0038] Figure 2 The capacity retention rate of NCM811 / Li batteries in Examples 1-5 and Comparative Examples 1-7 of this application after 250 cycles;
[0039] Figure 3 These are actual images of FM30, FM20, and FM20+FM30 before UV curing in the embodiments of this application;
[0040] Figure 4 The images shown are actual pictures of the products after UV curing of FM30, FM20, and FM20+FM30 in the embodiments of this application. Detailed Implementation
[0041] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0042] This application provides a membrane-supported flame-retardant gel polymer electrolyte, comprising a membrane substrate and a cross-linked gel layer loaded on the surface and / or inside the pores of the membrane substrate; the cross-linked gel layer comprises a polymer and a lithium salt electrolyte adsorbed within the cross-linked network of the polymer; the polymer comprises lithium sulfonate structural units, rigid structural units, and flexible structural units; the rigid structural unit comprises a first phosphorus-containing structural unit, and the flexible structural unit comprises a second phosphorus-containing structural unit and an ether oxygen structural unit; the mass percentage of phosphorus in the rigid structural unit is greater than the mass percentage of phosphorus in the flexible structural unit.
[0043] The diaphragm-supported flame-retardant gel polymer electrolyte of this application incorporates high-phosphorus rigid structural units, low-phosphorus flexible structural units, and lithium sulfonate structural units in the cross-linked gel layer. These units work synergistically with the diaphragm matrix to give the electrolyte high ionic conductivity, excellent flame retardancy, good interfacial stability, and resistance to swelling. Specifically: 1) The high-phosphorus rigid structural units construct a rigid, high-phosphorus gel framework, significantly improving the electrolyte's flame retardancy and high-temperature dimensional stability; 2) The low-phosphorus flexible structural units optimize the compatibility between the gel and the electrolyte, enhancing liquid absorption and retention capacity, while also imparting appropriate flexibility to the gel, overcoming the brittleness and cracking issues of a pure high-phosphorus framework; 3) The lithium sulfonate structural units provide ion conduction sites, regulating the interfacial lithium salt dissociation and ion transport environment, and reducing the electrode-electrolyte interfacial impedance; 4) The diaphragm provides stable mechanical support, ensuring overall thickness uniformity, giving the electrolyte puncture resistance, and preventing the cross-linked gel network from fragmenting. The synergistic matching of the above three types of functional structural units forms a rigid-flexible cross-linked polymer network. Combined with the mechanical reinforcement of the membrane matrix, it simultaneously achieves high ionic conductivity, excellent flame retardant properties, good interfacial stability, and swelling resistance.
[0044] It should be noted that the lithium salt electrolyte is adsorbed within the cross-linked network of the polymer, rather than simply placed on the outer surface of the cross-linked gel layer. The cross-linked network of the polymer simultaneously contains immobilized lithium sulfonate groups, phosphorus-containing polar groups, and ether oxygen segments. These polar sites undergo physical adsorption and local coordination with the electrolyte solvent and lithium salt ions, forming a confined liquid phase within the network. Furthermore, the cross-linked structure itself imposes spatial constraints on liquid phase migration, thereby reducing free flow.
[0045] In this embodiment, based on the total mass of the polymer, the mass percentage of lithium sulfonate structural units in the polymer is 5%~25%, the mass percentage of rigid structural units is 15%~40%, and the mass percentage of flexible structural units is 35%~70%. By adjusting the mass percentages of lithium sulfonate structural units, rigid structural units, and flexible structural units within the polymer to the aforementioned ranges, the lithium sulfonate structural units optimize the ion conduction environment, the rigid structural units enhance flame retardancy and thermal stability, and the flexible structural units improve liquid absorption capacity and membrane flexibility. These three elements work synergistically to further improve the ionic conductivity, flame retardancy, interfacial stability, and swelling resistance of the membrane-supported flame-retardant gel polymer electrolyte.
[0046] For example, the mass percentage of lithium sulfonate structural units in the polymer can be 5%, 10%, 15%, 20%, 25%, or a range between any two of the above values.
[0047] For example, the mass percentage of rigid structural units in the polymer can be 15%, 20%, 25%, 30%, 35%, 40%, or a range between any two of the above values.
[0048] For example, the mass percentage of flexible structural units in the polymer can be 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, or any range between any two of the above values.
[0049] It should be noted that the above polymer is obtained by free radical addition copolymerization of lithium sulfonate monomer, phosphorus-containing rigid monomer, and phosphorus-containing flexible monomer. This copolymerization process involves only carbon... The opening and addition of carbon double bonds results in almost all monomers participating in copolymerization joining the polymer molecular chain to form corresponding structural units. Without considering trace amounts of unreacted monomers, the mass percentage of monomers added is approximately equal to the mass percentage of the corresponding structural unit in the polymer chain after polymerization. Therefore, the proportions represented by the mass percentage of comonomers in this application can equivalently reflect the mass percentage relationship of each structural unit within the polymer. Those skilled in the art can then... The polymer was tested, and the actual mass percentage of each structural unit was calculated to verify the above feeding ratio results.
[0050] In some embodiments, the phosphorus content in the rigid structural unit is 10% to 14% by mass, while the phosphorus content in the flexible structural unit is 5% to 8% by mass. Maintaining the phosphorus content in both the rigid and flexible structural units within these ranges facilitates a gradient distribution of phosphorus within the gel network. The rigid structural unit with a higher phosphorus content can better and continuously provide flame-retardant and heat-resistant skeletal support, while the flexible structural unit retains the good compatibility of the flexible network with the electrolyte, its liquid absorption performance, and enhances the flexibility of the membrane-supported flame-retardant gel polymer electrolyte. This further improves the ionic conductivity, flame-retardant properties, interfacial stability, and swelling resistance of the membrane-supported flame-retardant gel polymer electrolyte.
[0051] For example, the mass percentage of phosphorus in the rigid structural unit can be 10%, 11%, 12%, 13%, 14%, or any range between any two of the above values.
[0052] For example, the mass percentage of phosphorus in the flexible structural unit can be 5%, 6%, 7%, 8%, or a range between any two of the above values. In this embodiment, the total phosphorus content of the polymer can be tested using inductively coupled plasma optical emission spectrometry (ICP-OES); combined with hydrogen nuclear magnetic resonance spectroscopy... Phosphorus-31 NMR spectrum By obtaining the molar percentage of each structural unit and the molar ratio of different phosphorus, the mass percentage of phosphorus in the rigid structural unit and the mass percentage of phosphorus in the flexible structural unit are calculated.
[0053] In some embodiments, the lithium sulfonate structural unit includes a lithium 2-acrylamide-2-methylpropanesulfonate structural unit. This structural unit can introduce fixed lithium sulfonate groups and lithium-ion sites into the crosslinked polymer network, which is beneficial for improving the lithium-ion transport environment in the gel network and for enhancing lithium-ion migration and interface stability.
[0054] In some embodiments, the first phosphorus-containing structural unit includes a first acrylate phosphate structural unit and a first ammonium phosphate structural unit; the second phosphorus-containing structural unit includes a second acrylate phosphate structural unit and a second ammonium phosphate structural unit. The flexible structural unit contains both phosphorus-containing groups and ether oxygen segments. The longer polyether chains can improve the flexibility of the system and its wetting and liquid absorption capacity for the electrolyte.
[0055] In some embodiments, the membrane substrate includes at least one of olefin porous membrane, ceramic-modified polyolefin porous membrane, and polyimide porous membrane. These membrane substrates are porous commercial membrane materials with interconnected pores that can absorb and retain electrolyte; ceramic and polyimide materials can appropriately improve high-temperature resistance and puncture resistance, and multiple substrate types are suitable for different battery cell application scenarios.
[0056] In some embodiments, the membrane substrate includes at least one of polyethylene membrane, polypropylene membrane, polypropylene / polyethylene / polypropylene three-layer composite membrane, ceramic-coated polyethylene membrane, ceramic-coated polypropylene membrane, and polyimide porous membrane.
[0057] In some embodiments, the membrane substrate has a thickness of 9-40 μm and a porosity of 35%-70%. This allows for sufficient space to load the crosslinked gel while providing mechanical support and preventing the gel layer from breaking, thus balancing the requirements for a thin battery cell with electrolyte storage capacity.
[0058] For example, the thickness of the membrane substrate can be 9 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, or a range of any two of the above values.
[0059] In the embodiments of this application, the combination of multiple lithium salts can be adapted to different voltage systems. A moderate lithium salt concentration can balance ion conduction efficiency, alleviating the problems of increased viscosity at high concentrations and insufficient charge carriers at low concentrations, thus balancing conductivity and stability. In some embodiments, the lithium salt in the lithium salt electrolyte is selected from... , LiFSI, LiTFSI, LiDFOB, LiBOB, At least one of the following. The concentration of lithium salt in the lithium salt electrolyte is 0.8-1.5%. .
[0060] For example, the concentration of lithium salt in the lithium salt electrolyte can be 0.8%. 0.9 1 1.1 1.2 1.3 1.4 1.5 , or the range formed between any two of the above values.
[0061] In this embodiment of the application, structural verification preferably includes: using FTIR to confirm the C=C conversion before and after curing; using XPS or elemental analysis to confirm the coexistence of P, N and S elements; using Karl Fischer and headspace analysis to confirm the moisture and volatile ammonia after drying; using cross-sectional SEM to observe the extent to which the gel network enters the membrane pores; and using leachate analysis to evaluate the migration of P, N and S components.
[0062] This application embodiment also provides a method for preparing the above-mentioned membrane-supported flame-retardant gel polymer electrolyte, comprising the following steps: S1, preparing a mixture containing lithium sulfonate monomer, phosphorus-containing rigid monomer, and phosphorus-containing flexible monomer; immersing a membrane substrate in the mixture for copolymerization and crosslinking reaction, forming a polymer on the surface and / or inside the pores of the membrane substrate, thereby obtaining a membrane-supported flame-retardant gel polymer electrolyte matrix; the lithium sulfonate monomer and the phosphorus-containing rigid monomer both contain unsaturated bonds, the phosphorus-containing flexible monomer contains unsaturated bonds and ether oxygen bonds, and the phosphorus content of the phosphorus-containing rigid monomer is greater than the phosphorus content of the phosphorus-containing flexible monomer; S2, immersing the membrane-supported flame-retardant gel polymer electrolyte matrix in a lithium salt electrolyte, allowing the polymer to adsorb the lithium salt electrolyte, forming a crosslinked gel layer on the surface and / or inside the pores of the membrane substrate, thereby obtaining a membrane-supported flame-retardant gel polymer electrolyte.
[0063] In this embodiment, the rigid structural unit is formed by copolymerization and crosslinking of phosphorus-containing rigid monomers; the flexible structural unit is formed by copolymerization and crosslinking of phosphorus-containing flexible monomers; and the lithium sulfonate structural unit is formed by copolymerization and crosslinking of lithium sulfonate monomers. These structural units serve as repeating units of the polymer chain segments. The phosphorus-containing rigid monomer, phosphorus-containing flexible monomer, and lithium sulfonate monomer all contain unsaturated bonds, which may specifically include double bonds. The phosphorus-containing rigid monomer, phosphorus-containing flexible monomer, and lithium sulfonate monomer undergo copolymerization and crosslinking reactions through unsaturated bonds to form the aforementioned polymer.
[0064] In this embodiment of the application, based on a total mass of 100 parts of all monomers in the copolymerization crosslinking reaction, the phosphorus-containing rigid monomer is 15 to 40 parts (e.g., 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, or any range between any two of the above values), the phosphorus-containing flexible monomer is 35 to 70 parts (e.g., 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, or any range between any two of the above values), and the lithium sulfonate monomer is 5 to 25 parts (e.g., 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, or any range between any two of the above values).
[0065] In some embodiments, the lithium sulfonate monomer includes lithium 2-acrylamide-2-methylpropanesulfonate, which forms the above-mentioned lithium 2-acrylamide-2-methylpropanesulfonate structural unit through a copolymerization crosslinking reaction.
[0066] In some embodiments, the phosphorus-containing rigid monomer includes rigid monomers of phosphate acrylate and partially ammonium-treated rigid monomers of phosphate acrylate, and the phosphorus-containing flexible monomer includes flexible monomers of phosphate acrylate and partially ammonium-treated flexible monomers of phosphate acrylate. The preparation process of the partially ammonium-treated rigid monomer of phosphate acrylate includes: neutralizing the rigid monomer of phosphate acrylate with ammonia water, causing a neutralization reaction between some of the phosphate groups in the rigid monomer of phosphate acrylate and the ammonia water, to obtain the partially ammonium-treated rigid monomer of phosphate acrylate. The preparation process of the partially ammonium-treated flexible monomer of phosphate acrylate includes: neutralizing the flexible monomer of phosphate acrylate with ammonia water, causing a neutralization reaction between some of the phosphate groups in the flexible monomer of phosphate acrylate and the ammonia water, to obtain the partially ammonium-treated flexible monomer of phosphate acrylate.
[0067] In some embodiments, the above-mentioned mixture also includes a photoinitiator, and the copolymerization and crosslinking reaction is initiated by ultraviolet light in the presence of the photoinitiator. The photoinitiation conditions are mild, the reaction rate is easy to control, and crosslinked polymers can be uniformly formed in the pores and surface of the diaphragm, resulting in a more uniform distribution of the gel layer and reducing the likelihood of localized over-crosslinking and embrittlement.
[0068] In some embodiments, step S1 includes: preparing a mixture containing lithium sulfonate monomer, phosphorus-containing rigid monomer, phosphorus-containing flexible monomer, and photoinitiator; immersing the membrane substrate in the mixture and performing double-sided ultraviolet curing under oxygen-isolated or low-oxygen conditions, thereby undergoing a copolymerization crosslinking reaction initiated by unsaturated bonds to form a polymer in situ on the surface and / or inside the pores of the membrane substrate, thus obtaining a membrane-supported flame-retardant gel polymer electrolyte matrix.
[0069] In some embodiments, the photoinitiator is 0.5%-3.0% of the total mass of the above-mentioned reaction components, and the photoinitiator is selected from at least one of 2-hydroxy-2-methylphenylacetone, 1-hydroxycyclohexylphenyl ketone, and 2,2-dimethoxy-2-phenylacetophenone.
[0070] In some embodiments, the mixture in step S1 further includes anhydrous acetonitrile, which is used as a temporary co-solvent. The amount of anhydrous acetonitrile is 5%-20% of the total mass of the reaction components, preferably 8%-15%. The lithium sulfonate monomer is first dissolved or uniformly dispersed in anhydrous acetonitrile, and then mixed with a phosphorus-containing rigid monomer, a phosphorus-containing flexible monomer, and a photoinitiator to obtain a photocuring precursor solution (i.e., the mixture). Subsequently, the membrane substrate is immersed in the photocuring precursor solution, first vacuum-impregnated at -0.04 to -0.09 MPa for 5-20 min, and then irradiated with 365 nm ultraviolet light from both sides of the membrane substrate for 5-20 min respectively; a copolymerization crosslinking reaction occurs under the initiation of the photoinitiator, forming a polymer on the surface and / or inside the pores of the membrane substrate, to obtain a membrane-supported flame-retardant gel polymer electrolyte matrix.
[0071] In some embodiments, before immersing the membrane-supported flame-retardant gel polymer electrolyte matrix into the lithium salt electrolyte in step S2, the membrane-supported flame-retardant gel polymer electrolyte matrix is vacuum dried at 40-60°C and -0.08~-0.095 MPa for 24-48 h to remove acetonitrile and residual volatile components. Preferably, the residual acetonitrile content is not higher than 1000 ppm, more preferably not higher than 500 ppm.
[0072] In this embodiment, the preparation process of partially ammonium-modified rigid monomers of phosphate acrylate includes: neutralizing the rigid monomers of phosphate acrylate with ammonia water, causing the phosphate groups in the rigid monomers of phosphate acrylate to undergo a neutralization reaction with ammonia water, thereby obtaining partially ammonium-modified rigid monomers of phosphate acrylate. The preparation process of partially ammonium-modified flexible monomers of phosphate acrylate includes: neutralizing the flexible monomers of phosphate acrylate with ammonia water, causing the phosphate groups in the flexible monomers of phosphate acrylate to undergo a neutralization reaction with ammonia water, thereby obtaining partially ammonium-modified flexible monomers of phosphate acrylate. The neutralization of ammonia water with the acidic groups of phosphate to form an ammonium phosphate salt structure can reduce the free acidity of the material, improve the miscibility between lithium sulfonate monomers and phosphorus monomers, enhance the wetting and penetration ability of the monomers into the membrane pores, and facilitate the formation of a uniform gel network.
[0073] In this embodiment, the preparation process of the partially ammonium-modified acrylate phosphate rigid monomer specifically includes the following steps: Deionized water is added to the acrylate phosphate rigid monomer to form a dispersion system; ammonia water with a mass fraction of 5%-25% is added dropwise at 5-30℃; during the process, samples are continuously taken to prepare a 10% aqueous dispersion for pH testing until the pH of the dispersion is 6.8-8.0; this helps avoid excessive local alkalinity that could damage the acrylic double bonds, reduces monomer by-decomposition, smoothly completes acid-base neutralization, and fully preserves the polymerization active sites. Stirring continues for 30-120 min; then drying is carried out at 40-60℃, followed by vacuum drying at 45-65℃ and -0.08~-0.095 MPa for 24-48 h to obtain the modified rigid monomer. The preparation process of partially ammonium-modified acrylate phosphate flexible monomers includes the following steps: Deionized water is added to the acrylate phosphate flexible monomers to form a dispersion system. Ammonia water with a mass fraction of 5%-25% is added dropwise at 5-30℃. During this process, samples are continuously taken to prepare a 10% aqueous dispersion for pH testing until the pH of the dispersion reaches 6.8-8.0. This helps avoid excessive local alkalinity that could damage the acrylate double bonds, reduces monomer by-decomposition, ensures stable acid-base neutralization, and fully preserves the polymerization active sites. Stirring continues for 30-120 min; then drying is carried out at 40-60℃, followed by vacuum drying at 45-65℃ and -0.08~-0.095 MPa for 24-48 h to obtain the modified flexible monomer. The above method combines pre-drying and vacuum drying to reduce the moisture and free ammonia introduced by the ammonia treatment, avoiding the direct introduction of large amounts of water into the lithium salt electrolyte.
[0074] In some embodiments, the partially ammonium-treated phosphate acrylate rigid monomer and the partially ammonium-treated phosphate acrylate flexible monomer meet at least one of the following criteria: 1) moisture content ≤ 500 ppm; 2) mass percentage of free ammonia or volatile alkaline components ≤ 0.10%; 3) acrylate double bond retention rate ≥ 95%. Lower moisture and residual alkali can avoid interfering with lithium salt stability and suppress side reactions; higher double bond retention rate can ensure sufficient copolymer crosslinking, maintain the integrity of the gel network structure, and stably exert flame retardant and ion-conducting effects.
[0075] This application also provides a lithium battery, including a positive electrode, a negative electrode, and a flame-retardant gel polymer electrolyte supported by a separator. The flame-retardant gel polymer electrolyte supported by the separator is located between the positive electrode and the negative electrode. The flame-retardant gel polymer electrolyte supported by the separator includes the above-mentioned flame-retardant gel polymer electrolyte supported by the separator or the flame-retardant gel polymer electrolyte supported by the separator prepared by the above-mentioned preparation method.
[0076] This lithium battery arranges a flame-retardant gel polymer electrolyte supported by a separator between the positive and negative electrodes. This combines the structural separation function of the separator with the ion conduction function of the gel electrolyte, thereby forming a continuous and stable ion transport channel between the electrodes. Because the gel polymer electrolyte can stably adsorb lithium salt electrolyte on the separator surface and inside the pores, and constrain the free electrolyte, the fluidity, leakage risk, and swelling tendency of the electrolyte layer are reduced, thus improving the contact stability of the electrode interface and the dimensional retention during cycling. Therefore, this lithium battery can balance flame retardancy, structural support, and electrochemical transport performance, and exhibits better safety and cycle reliability under high temperature, overcharge, or long-term cycling conditions.
[0077] In some embodiments, the positive electrode sheet includes a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode active material; the positive electrode active material includes , , , , , At least one of them.
[0078] In some embodiments, the negative electrode sheet includes a negative electrode active material layer, which includes a negative electrode active material; the negative electrode active material includes at least one of lithium metal, graphite, silicon carbide, hard carbon, and lithium titanate.
[0079] In some embodiments, the lithium battery includes at least one of lithium metal batteries, high-voltage lithium-ion batteries, high-safety energy storage lithium batteries, and flame-retardant lithium batteries.
[0080] The present application will be further described below through specific embodiments. These embodiments are used to illustrate the composition, preparation, and evaluation methods, and do not limit the scope of protection.
[0081] The sources of raw material information in each embodiment and comparative example are as follows:
[0082] The FM20 (i.e., rigid monomer of acrylate phosphate) used in this application is NTCADD. FM20 and FM30 (i.e., flexible monomers of acrylate phosphate) are NTCADD Both FM20 and FM30 were purchased from Beijing Baiyuan Chemical Co., Ltd. FM20 is a commercial mixture of phosphate acrylates, typically containing approximately 12% phosphorus with an effective content greater than 99.5%, serving as a source of a high-phosphorus, relatively rigid phosphorus-containing hard skeleton. FM30 is also a commercial mixture of phosphate acrylates, typically containing approximately 6.5% phosphorus with an effective content not less than 99.5%, and containing longer ether oxygen segments, serving as a source of a flexible phosphorus-containing soft skeleton. Neither FM20 nor FM30 corresponds to a single CAS number. Ammonia-neutralized FM20 is designated as N-FM20 (i.e., partially ammonium-treated rigid monomer of phosphate acrylate), and ammonia-neutralized FM30 is designated as N-FM30 (i.e., partially ammonium-treated flexible monomer of phosphate acrylate). Ammonia neutralization refers to adjusting the pH of the FM20 or FM30 aqueous dispersion system to near neutral using ammonia water, causing at least some of the acidic phosphate groups of FM20 or FM30 to form ammonium salts, followed by the removal of free water and free ammonia.
[0083] Table 1
[0084]
[0085] It should be noted that FM20 and FM30 are both commercial mixtures and therefore not limited by a single CAS number; N-FM20, N-FM30, and AMPSLi are all intermediate products obtained according to the method of this application and are not purchased separately as commercial raw materials. Porous commercial separators, NCM811, and LPO5 commercial liquid electrolytes are also composite commercial materials, and their CAS information is listed according to the main chemical components or the product instructions, COA, or SDS provided by the supplier.
[0086] Example 1
[0087] The preparation method of the diaphragm-supported flame-retardant gel polymer electrolyte in this embodiment includes the following steps:
[0088] 1. Preparation of AMPSLi lithium salt monomer:
[0089] Weigh 4.14 g AMPS and dissolve it in 50 mL of deionized water to obtain a sulfonic acid monomer solution. Dissolve 0.84 g lithium hydroxide monohydrate in 50 mL of deionized water to obtain a lithium source solution. Slowly add the lithium source solution dropwise to the sulfonic acid monomer solution and stir at 45 °C for 12 h to neutralize the reaction. Remove most of the water by rotary evaporation, and vacuum dry at 50–65 °C for 24–48 h, controlling the moisture content to ≤300 ppm, to obtain AMPSLi. Store in a sealed container protected from light. The dropping rate of the lithium source solution in this step is not specifically limited and can be conventionally adjusted according to the exothermic reaction of the system.
[0090] 2. Preparation of FM20 and FM30 ammonia neutralization modifications (N-FM20, N-FM30):
[0091] Take 10 g of FM20 and add deionized water at a mass ratio of FM20 to water of 1:0.1~0.8, and stir to form a homogeneous system. At 15~25℃, slowly add 15% ammonia water to the homogeneous system at a dropping rate of 2.0 mL / min. Take samples intermittently to prepare a 10wt% aqueous dispersion to measure the pH and adjust it to 7.0~7.5. Keep warm and stir for 60 min to complete the neutralization reaction. Pre-dry the product obtained from the neutralization reaction in an oven at 55℃ for 10 h to remove free water. Then vacuum dry at 60℃ and -0.095MPa for 36 h until the mass is basically constant to obtain N-FM20.
[0092] FM30 was processed using the same steps and conditions as FM20 to obtain N-FM30. Both N-FM20 and N-FM30 met the following quality control standards: moisture ≤300 ppm, free ammonia ≤0.10 wt%, and acrylate double bond retention rate ≥95%.
[0093] The ammonia neutralization process described above should be carried out at a temperature not exceeding 65°C and protected from light to reduce the thermal self-polymerization of double bonds. The processed product should be stored in a dark, low-temperature, and sealed environment. The dropping rate of the ammonia solution is not specifically limited, but a slow increase in the system pH is preferable to control the uneven reaction caused by localized strong alkali.
[0094] 3. Preparation of membrane-supported flame-retardant gel polymer electrolyte:
[0095] S1. Dissolve or uniformly disperse 0.15g AMPSLi in 0.1g anhydrous acetonitrile to form an acetonitrile solution of AMPSLi. Acetonitrile is not used as the main liquid phase component in the final electrolyte and is removed by vacuum drying after photocuring. Subsequently, add 0.2g N-FM20 and 0.55g N-FM30 to the acetonitrile solution of AMPSLi sequentially, followed by 13.5mg 2-hydroxy-2-methylphenylacetone (HMPP). Stir for 30 minutes in the dark to form a homogeneous photocuring precursor solution. The amount of anhydrous acetonitrile used is 5%-20% of the total mass of the reaction components, which can reduce the viscosity of the system, improve wetting, and facilitate subsequent vacuum removal.
[0096] S2. After cutting the ceramic-coated PE diaphragm (hereinafter referred to as the diaphragm substrate), vacuum dry it at 70℃ for 24 h. Completely immerse the dried diaphragm substrate in the photocuring precursor solution and vacuum impregnate it for 10 min at -0.09 MPa to allow the photocuring precursor solution to enter the pores of the diaphragm substrate. Remove the diaphragm substrate and scrape or roll it to remove excess photocuring precursor solution from the surface.
[0097] S3. The impregnated membrane substrate is sandwiched between FEP release films or quartz sheets to reduce oxygen inhibition polymerization. 365nm ultraviolet light is used to irradiate both sides for 10 min to cause N-FM20, N-FM30 and AMPSLi to undergo free radical copolymerization reaction and form a phosphorus-sulfonate-containing lithium crosslinked gel network (i.e., crosslinked gel layer) fixed on the membrane pores and surface to obtain a photocurable composite membrane.
[0098] S4. The photocurable composite diaphragm was vacuum dried at 55℃ and -0.095MPa for 36h to remove acetonitrile and residual volatile components; the residual acetonitrile content was not higher than 1000ppm. Then it was transferred to an inert atmosphere glove box and immersed in LPO5 commercial liquid electrolyte for 18h. After removal, the surface free liquid was removed to obtain a diaphragm-supported flame-retardant gel polymer electrolyte.
[0099] Figure 3 These are actual photos of FM30, FM20, and FM20+FM30 mixtures before curing (from left to right: FM30, FM20, and FM20+FM30 mixture). (From...) Figure 3 It can be seen that the above-mentioned material before UV curing is a homogeneous liquid with good fluidity, which can fully wet the pores of the diaphragm.
[0100] Figure 4 These are physical images of the products cured under UV light for FM30, FM20, and FM20+FM30 mixtures (from left to right: products cured under UV light for FM30, FM20, and FM20+FM30). Figure 4 It can be seen that the FM20 cured gel exhibited obvious yellowing, while the FM30 and FM20+FM30 cured gels had a uniform and intact appearance, indicating that the combination of FM20 and FM30 can effectively inhibit gel yellowing and obtain a structurally stable cross-linked gel.
[0101] Examples 2-5
[0102] The following formulations are based on a batch size of 0.90 g of N-FM20, N-FM30, and AMPSLi. HMPP is 1.5% of the total mass of the reactive components. The effects of the hard-soft hybrid gel network on flame retardancy, liquid absorption and retention capacity, ion transport, and battery cycle stability were investigated by adjusting the ratio of the N-FM20 hard framework, N-FM30 soft framework, and AMPSLi ion sites in each embodiment.
[0103] Except for the formulation and diaphragm type set as shown in Table 2, the remaining steps are the same as in Example 1. Example 2 increases the N-FM30 ratio to enhance flexibility and liquid absorption; Example 3 increases the N-FM20 ratio to enhance flame retardancy and thermal dimensional stability; Example 4 increases the AMPSLi ratio to enhance ion regulation; Example 5 changes the supporting diaphragm and appropriately reduces the AMPSLi ratio to examine the coupling effect between the support and the ratio of soft to hard skeleton.
[0104] Table 2
[0105]
[0106] Comparative Examples 1-7
[0107] Except for the differences set in Table 3, the remaining steps are the same as in Example 1.
[0108] Table 3
[0109]
[0110] The membrane-supported flame-retardant gel polymer electrolytes prepared in the above embodiments and comparative examples were subjected to the following performance tests:
[0111] 1. pH, moisture and residual volatile alkali: The monomer sample was prepared into a 10% aqueous dispersion and the pH of the dispersion was determined; the moisture content was tested by Karl Fischer titration; free ammonia or volatile basic components were quantitatively detected by headspace gas chromatography or acid absorption titration. The results are shown in Table 4.
[0112] 2. Electrolyte absorption rate and retention rate: Record the mass m0 of the dry-state diaphragm-supported flame-retardant gel polymer electrolyte; immerse the dry sample in the corresponding lithium salt electrolyte until fully saturated, remove it, wipe off the free electrolyte on the surface, and weigh the mass m1 of the sample after saturation; then let the saturated sample stand for 24 hours under a specified pressure, and weigh the mass m2 of the sample after standing. The absorption rate = ×100%; Liquid retention rate = ( () × 100%, the results are shown in Table 5.
[0113] 3. Thermal dimensional stability: The sample was treated at 120℃ for 30 min, and the area change before and after treatment was measured. The gel network was observed to see if it oozes out, cracks or delaminates. The results are shown in Table 5.
[0114] 4. Flame retardant performance: Under the same size and electrolyte load, the sample was ignited with an open flame for 3 seconds. After the flame source was removed, the self-extinguishing time of the sample was recorded, and the char morphology of the sample was observed. The results are shown in Table 5.
[0115] 5. Ionic conductivity: Electrochemical impedance spectroscopy was performed on assembled stainless steel / gel polymer electrolyte / stainless steel (SS / GPE / SS) batteries to obtain the bulk impedance R; L is the gel electrolyte thickness, and A is the effective contact area, according to... The calculations are shown in Table 6.
[0116] 6. Lithium-ion transference number: The lithium-ion transference number of the assembled lithium metal / gel polymer electrolyte / lithium metal (Li / GPE / Li) symmetric cells was calculated using the Bruce-Vincent method. The results are shown in Table 6.
[0117] 7. Electrochemical stability window: Assemble a lithium metal / gel polymer electrolyte / stainless steel (Li / GPE / steel sheet) half-cell and use linear sweep voltammetry with a scan rate of 1. The upper limit of the scanning voltage was set to 6.0 V, and the voltage corresponding to the obvious oxidation decomposition of the system was recorded to obtain the electrochemical stability window. The results are shown in Table 6.
[0118] 8. Lithium deposition-stripping cycle performance: Assembled Li / GPE / Li symmetric cells at a current density of 0.5 Surface capacity 0.5 Constant current lithium deposition-stripping cycling was performed under these conditions, and the time it took for the battery to cycle stably was recorded. The results are shown in Table 6.
[0119] Preparation of Li coin cell:
[0120] Positive electrode active material Conductive carbon black Super-P and PVDF binder are added in a mass ratio of 85:10:5 with N-methyl-2-pyrrolidone to prepare a positive electrode slurry; this slurry is coated onto an aluminum foil current collector, dried, rolled, and stamped to obtain the positive electrode sheet.
[0121] Inside an argon glove box where both water and oxygen content are <0.1ppm, the positive electrode shell... shrapnel gasket The above positive electrode sheet Membrane-supported flame-retardant gel polymer electrolyte Lithium metal anode sheet The negative electrode shells are stacked sequentially and sealed; the gel electrolyte has pre-adsorbed the lithium salt electrolyte, so no additional liquid electrolyte is added during assembly, resulting in... / Li button cell.
[0122] Preparation of NCM811 / Li coin cell:
[0123] Positive electrode active material Replace with an equal amount of NCM811, and the remaining steps and conditions are the same as above. The same method as for the Li coin cell was used to prepare the NCM811 / Li coin half cell.
[0124] Coin cell half-cell cycle testing: including 0.1C first-cycle discharge capacity, 1C first-cycle discharge capacity, 250-cycle discharge capacity, 1C capacity retention, and average coulombic efficiency. The Li half-cell was tested at 2.5–4.0 V, and the results are shown in Table 7. Figure 1 The NCM811 / Li half-cell was tested at 2.8-4.3 V, and the positive electrode loading was 1.5-3. Among them, the positive electrode loading refers to the mass of positive electrode active material per unit effective area of the positive electrode sheet. The test results are shown in Table 8 and Figure 2 .
[0125] Table 4
[0126]
[0127] Table 5
[0128]
[0129] Table 6
[0130]
[0131] Table 7
[0132]
[0133]
[0134] Table 8
[0135]
[0136]
[0137] Data shows that Example 1, with a mass ratio of N-FM20, N-FM30, and AMPSLi of 20:55:15, achieved a relatively balanced soft-hard bonded network structure, a liquid absorption rate of 268%, a 24-hour liquid retention rate of 93.5%, a thermal shrinkage rate of 2.1% at 120°C, self-extinguishing approximately 1.5 seconds after removal from the flame, and a room temperature ionic conductivity of 2.21 × 10⁻⁶. With a lithium-ion transference number of 0.69, it exhibits a comprehensive balance of flame retardancy, ion transport, and network integrity.
[0138] Example 2, with an increased N-FM30 ratio, exhibited higher liquid absorption and higher ionic conductivity, indicating that the flexible phosphorus-containing soft skeleton is beneficial for improving wettability and ion transport. Example 3, with an increased N-FM20 ratio, showed shorter self-extinguishing time and lower thermal shrinkage, indicating that the rigid phosphorus-containing hard skeleton is beneficial for enhancing flame retardancy and thermal dimensional stability, but the higher network rigidity slightly reduced liquid absorption and ionic conductivity. Example 4, with an increased AMPSLi ratio, increased the lithium-ion transference number to 0.73, but slightly increased liquid absorption swelling and thermal shrinkage.
[0139] Comparative Example 1 used FM20 and FM30 that had not been neutralized with ammonia and thoroughly dried. Due to the strong free acidity and insufficient control of moisture / volatile components, the electrochemical window decreased, the interfacial impedance increased, and the stability time and full-cell cycle performance of the Li / GPE / Li symmetric battery significantly declined. This indicates that neutralization and deep drying are necessary process steps for the normal operation of the battery system. Comparative Example 2 lacked N-FM20, resulting in insufficient contribution from the hard framework and decreased flame retardancy and thermal stability. Comparative Example 3 lacked N-FM30, resulting in insufficient contribution from the soft framework and decreased liquid absorption, flexibility, and uniform curing. Comparative Example 4 lacked AMPSLi, resulting in a significant decrease in lithium-ion transference number. Comparative Example 5 did not form a photocrosslinked network, resulting in the worst liquid retention and cycle stability. Comparative Example 6 was a traditional separator / liquid electrolyte system with a high risk of thermal shrinkage and combustion. Comparative Example 7 lacked separator support, resulting in insufficient mechanical integrity and cycle stability.
[0140] Under the proposed test conditions, the Li / GPE / Li symmetric cell of Example 1 achieved a stable time of approximately 900 hours; the NCM811 / Li cell had a first-cycle discharge capacity of approximately 206.8 kWh at 0.1C. After switching to cycle 1C, the capacity in the first cycle is approximately 190.6. 250 laps, capacity approximately 163.2. The capacity retention rate was approximately 85.6%. Compared with the comparative example, the soft-hard combined N-FM20 / N-FM30 / AMPSLi gel network can simultaneously reduce free electrolyte migration, improve flame retardancy, and enhance interfacial stability.
[0141] The above embodiments are only used to illustrate the technical solution of this application. Without departing from the core concept of this application, reasonable adjustments to the ammonia concentration, pH range, drying temperature, FM20FM30 ratio, diaphragm type, photoinitiation conditions, and liquid electrolyte composition can all be incorporated into the technical concept of this application.
[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A membrane-supported flame-retardant gel polymer electrolyte, characterized in that, Includes a membrane substrate and a cross-linked gel layer loaded on the surface and / or inside the pores of the membrane substrate; The cross-linked gel layer includes a polymer and a lithium salt electrolyte adsorbed within the cross-linked network of the polymer. The polymer includes lithium sulfonate structural units, rigid structural units, and flexible structural units; The rigid structural unit includes a first phosphorus-containing structural unit, and the flexible structural unit includes a second phosphorus-containing structural unit and an ether-oxygen structural unit. The mass percentage of phosphorus in the rigid structural unit is greater than that in the flexible structural unit.
2. The diaphragm-supported flame-retardant gel polymer electrolyte according to claim 1, characterized in that, Based on the total mass of the polymer, the mass percentage of the lithium sulfonate structural unit is 5%~25%, the mass percentage of the rigid structural unit is 15%~40%, and the mass percentage of the flexible structural unit is 35%~70%. And / or, the mass percentage of phosphorus in the rigid structural unit is 10%~14%; And / or, the phosphorus content in the flexible structural unit is 5% to 8% by mass.
3. The membrane-supported flame-retardant gel polymer electrolyte according to claim 1 or 2, characterized in that, The first phosphorus-containing structural unit includes a first acrylate phosphate structural unit and a first ammonium phosphate structural unit; the second phosphorus-containing structural unit includes a second acrylate phosphate structural unit and a second ammonium phosphate structural unit. And / or, the lithium sulfonate structural unit includes a lithium 2-acrylamide-2-methylpropanesulfonate structural unit.
4. The membrane-supported flame-retardant gel polymer electrolyte according to claim 1 or 2, characterized in that, The membrane substrate includes at least one of olefin porous membrane, ceramic-modified polyolefin porous membrane, and polyimide porous membrane; And / or, the thickness of the membrane substrate is 9~40μm, and the porosity is 35%~70%; And / or, the lithium salt in the lithium salt electrolyte is selected from... , LiFSI, LiTFSI, LiDFOB, LiBOB, At least one of them; And / or, the concentration of lithium salt in the lithium salt electrolyte is 0.8-1.5%. .
5. A method for preparing a membrane-supported flame-retardant gel polymer electrolyte according to any one of claims 1-4, characterized in that, Includes the following steps: S1. Prepare a mixture containing lithium sulfonate monomer, phosphorus-containing rigid monomer, and phosphorus-containing flexible monomer; immerse the membrane substrate in the mixture for copolymerization and crosslinking reaction to form a polymer on the surface and / or inside the pores of the membrane substrate, thereby obtaining a membrane-supported flame-retardant gel polymer electrolyte matrix. The lithium sulfonate monomer and the phosphorus-containing rigid monomer both contain unsaturated bonds, and the phosphorus-containing flexible monomer contains unsaturated bonds and ether oxygen bonds. The phosphorus element mass percentage content in the phosphorus-containing rigid monomer is greater than the phosphorus element mass percentage content in the phosphorus-containing flexible monomer. S2. Immerse the membrane-supported flame-retardant gel polymer electrolyte matrix into a lithium salt electrolyte, so that the cross-linked network of the polymer adsorbs the lithium salt electrolyte, thereby obtaining the membrane-supported flame-retardant gel polymer electrolyte.
6. The preparation method according to claim 5, characterized in that, Based on a total mass of 100 parts of all monomers in the copolymerization and crosslinking reaction, the phosphorus-containing rigid monomer is 15-40 parts, the phosphorus-containing flexible monomer is 35-70 parts, and the lithium sulfonate monomer is 5-25 parts. And / or, the lithium sulfonate monomer comprises lithium 2-acrylamide-2-methylpropanesulfonate.
7. The preparation method according to claim 5 or 6, characterized in that, The phosphorus-containing rigid monomer includes rigid phosphate acrylate monomers and partially ammonium-salted rigid phosphate acrylate monomers, and the phosphorus-containing flexible monomers include flexible phosphate acrylate monomers and partially ammonium-salted flexible phosphate acrylate monomers. The preparation process of the partially ammonium-salted rigid monomer of acrylate includes: neutralizing the rigid monomer of acrylate with ammonia water, so that some of the phosphate groups in the rigid monomer of acrylate react with ammonia water to obtain the partially ammonium-salted rigid monomer of acrylate. The preparation process of the partially ammonium-salted acrylate phosphate flexible monomer includes: neutralizing the acrylate phosphate flexible monomer with ammonia water, so that some of the phosphate groups in the acrylate phosphate flexible monomer undergo a neutralization reaction with ammonia water to obtain the partially ammonium-salted acrylate phosphate flexible monomer. And / or, the copolymerization crosslinking reaction is initiated by ultraviolet light in the presence of a photoinitiator.
8. The preparation method according to claim 7, characterized in that, The preparation process of the partially ammonium-modified phosphate acrylate rigid monomer specifically includes the following steps: adding deionized water to the phosphate acrylate rigid monomer to form a dispersion system; adding 5%-25% ammonia water by mass dropwise at 5-30℃; continuously sampling and preparing a 10% aqueous dispersion to test the pH until the pH of the aqueous dispersion is 6.8-8.0; continuing to stir for 30-120 min; then drying at 40-60℃, and then vacuum drying at 45-65℃ and -0.08~-0.095 MPa for 24-48 h to obtain the partially ammonium-modified phosphate acrylate rigid monomer; And / or, the preparation process of the partially ammonium-modified phosphate acrylate flexible monomer specifically includes the following steps: adding deionized water to the phosphate acrylate flexible monomer to form a dispersion system, adding 5%-25% ammonia water by mass dropwise at 5-30℃, continuously sampling and preparing a 10% aqueous dispersion to detect the pH until the pH of the aqueous dispersion is 6.8-8.0; continuing to stir for 30-120 min; then drying at 40-60℃, and then vacuum drying at 45-65℃ and -0.08~-0.095 MPa for 24-48 h to obtain the partially ammonium-modified phosphate acrylate flexible monomer; And / or, the partially ammonium-treated phosphate acrylate rigid monomer and the partially ammonium-treated phosphate acrylate flexible monomer each independently satisfy at least one of the following indicators: 1) Moisture content ≤ 500 ppm; 2) The mass percentage of free ammonia or volatile alkaline components is ≤0.10% based on the total mass of monomers; 3) Acrylic double bond retention rate ≥95%.
9. A lithium battery, characterized in that, A flame-retardant gel polymer electrolyte comprising a positive electrode, a negative electrode, and a separator support, wherein the separator support flame-retardant gel polymer electrolyte is located between the positive electrode and the negative electrode, and the separator support flame-retardant gel polymer electrolyte includes the separator support flame-retardant gel polymer electrolyte according to any one of claims 1-4 or the separator support flame-retardant gel polymer electrolyte prepared by the preparation method according to any one of claims 5-8.
10. The lithium battery according to claim 9, characterized in that, The positive electrode sheet includes a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode active material; the positive electrode active material includes... , , , , , At least one of them; And / or, the negative electrode sheet includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material; the negative electrode active material includes at least one of lithium metal, graphite, silicon carbide, hard carbon, and lithium titanate; And / or, the lithium battery includes at least one of lithium metal batteries, high-voltage lithium-ion batteries, high-safety energy storage lithium batteries, and flame-retardant lithium batteries.
